1975
DOI: 10.1007/bf00152964
|View full text |Cite
|
Sign up to set email alerts
|

The height distribution of flare hard X-rays in thick and thin target models

Abstract: The current controversy between thick and thin target models of hard X-ray flares is reviewed and it is concluded that the most promising method of distinguishing them is in terms of the differences in the distribution of the source with height in the solar atmosphere.Quantitative predictions are made of this height distribution for both models and the results discussed in relation to observations of hard X-ray emission from flares behind the limb. It is concluded that the thick target model is as compatible w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Following accleration, electrons travel down the flare loop and undergo Coulomb collisions with the ambient plasma, reducing their energy from E 0 to E. Thus, at a given distance, z, along the loop, the spectrum becomes f (E, N(z)), where N(z) = − n(z)dz is the column depth and n(z) is the number density of the ambient plasma (Brown 1972). The energy lost to collisions is given by E 2 = E 2 0 − 2KN, (Brown 1972), where K = 2πe 4 Λ and Λ is the Coulomb logarithm for an ionised plasma, which is used here as observed emission originates from heights at which the solar atmosphere is well ionised (Brown & McClymont 1975;Emslie 1978).…”
Section: Thick Target Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following accleration, electrons travel down the flare loop and undergo Coulomb collisions with the ambient plasma, reducing their energy from E 0 to E. Thus, at a given distance, z, along the loop, the spectrum becomes f (E, N(z)), where N(z) = − n(z)dz is the column depth and n(z) is the number density of the ambient plasma (Brown 1972). The energy lost to collisions is given by E 2 = E 2 0 − 2KN, (Brown 1972), where K = 2πe 4 Λ and Λ is the Coulomb logarithm for an ionised plasma, which is used here as observed emission originates from heights at which the solar atmosphere is well ionised (Brown & McClymont 1975;Emslie 1978).…”
Section: Thick Target Modellingmentioning
confidence: 99%
“…During the rise phase of a typical flare, the flux of HXRs reaches a peak and the spectral index hardens (Parks & Winckler 1969;Benz 1977;Fletcher & Hudson 2002). Based on the theoretical derivations of nonthermal X-ray intensity with height in the coronal acceleration scenario (Brown & McClymont 1975), this is expected to result in a descent of the location of peak nonthermal emission in the time coming up to the HXR peak. It was suggested that this downward motion of nonthermal X-ray sources was observed in the C1.1 class early impulsive flare that occurred on 28 November 2002 (SOL2002-11-28T04:37, Sui et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To study possible effects of collisions, we compared the change in the electron spectrum and the resulting footpoint spectrum for collisional energy loss and energy loss due to the electric field. The change in the electron spectrum due to collisions depends on the column depth through which the beam passes and was computed by Leach & Petrosian (1981) and Brown & McClymont (1975). We assume a column depth derived from the density in the loop times half the loop length.…”
Section: Collisions and Other Possible Scenariosmentioning
confidence: 99%
“…X-ray source heights have previously been used to test models of accelerated electrons in the solar atmosphere. Brown & McClymont (1975) showed that X-ray source height measurements can potentially discriminate between the thick-and thin-target models. Similarly, and used source heights to derive a chromospheric density measurement directly from observed spectra with RHESSI (Lin et al 2002), with a similar analysis performed by Kontar, Hannah, & MacKinnon (2008) to measure field and density variations with height.…”
Section: Introductionmentioning
confidence: 99%